2013
DOI: 10.1002/hipo.22182
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of multiple memory systems: From neurotransmitters to metabolic substrates

Abstract: This article reviews evidence showing that neurochemical modulators can regulate the relative participation of the hippocampus and striatum in learning and memory tasks. For example, relative release of acetylcholine increases in the hippocampus and striatum reflects the relative engagement of these brain systems during learning of place and response tasks. Acetylcholine release is regulated in part by available brain glucose levels, which themselves are dynamically modified during learning. Recent findings su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 82 publications
4
40
0
Order By: Relevance
“…In addition, in view of the present findings, the question arises whether the gradual learning subserved by the DLS may be a function of number of trials, passage of time, or both. It may be speculated that the mere "passage of time" allotted by either a spaced training protocol or "extended training" protocol with many trials may be sufficient to allow for the gradual rise in striatal acetylcholine, as well as other temporally graded neurobiological processes (Gold et al, 2013), that may facilitate response learning and/or impair place learning. It is also possible that these factors are not mutually exclusive and that an interaction between number of trials and passage of time may govern the relative dominance of multiple memory systems.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in view of the present findings, the question arises whether the gradual learning subserved by the DLS may be a function of number of trials, passage of time, or both. It may be speculated that the mere "passage of time" allotted by either a spaced training protocol or "extended training" protocol with many trials may be sufficient to allow for the gradual rise in striatal acetylcholine, as well as other temporally graded neurobiological processes (Gold et al, 2013), that may facilitate response learning and/or impair place learning. It is also possible that these factors are not mutually exclusive and that an interaction between number of trials and passage of time may govern the relative dominance of multiple memory systems.…”
Section: Discussionmentioning
confidence: 99%
“…Gold and colleagues demonstrated that systemic or central glucose administration enhanced cognitive performance and memory in rats, and glucose had a high positive impact on patients with Alzheimer's disease and Down's syndrome [26]. In addition, an essential role for glycogenolysis in memory processing was demonstrated by inhibition of glycogen phosphorylase with 1,4-dideoxy-1,4-amino-d-arabinitol (DAB) [23,48,64], and this conclusion is strongly reinforced by discovery of defects in long term memory formation in mice lacking brain glycogen synthase [20].…”
Section: Glucose Glycogen Lactate and Memorymentioning
confidence: 97%
“…There is considerable evidence that acetylcholine release contributes to a wide range of learning and memory categories, regulating the participation of multiple neural systems during cognitive processing (Gold et al, 2013). The examination of glucose effects on acetylcholine release has been assessed in the hippocampus in relation to both spontaneous alternation and inhibitory avoidance training.…”
Section: Glucose Actions In the Brain Contributing To Memory Enhancementmentioning
confidence: 99%
“…Bélanger et al, 2011; Magistretti, 2006; Pellerin et al, 2007; Gibbs et al, 2008; Pirttimaki and Parri, 2013; Bezzi and Volterra, 2011; Gold and Korol, 2012; Gold et al, 2013). These findings support a sequence by which glucose is taken into astrocytes for production of glycogen stores, with glycogenolysis and production of lactate initiated during learning by activation of neurotransmitter membrane receptors on astrocytes.…”
Section: Glucose Actions In the Brain Contributing To Memory Enhancementmentioning
confidence: 99%